2011
DOI: 10.1519/jsc.0b013e3181b94a3d
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plyometric Training on Power and Kicking Distance in Female Adolescent Soccer Players

Abstract: The purpose of this study was to measure the effects of low-frequency, low-impact plyometric training on vertical jump (VJ) and kicking distance in female adolescent soccer players. Sixteen adolescent soccer players were studied (age 13.4 ± 0.5 years) across 14 weeks. The control group (general soccer training only) had 6 subjects, and the plyometric training (general soccer training plus plyometric exercise) group had 10 subjects. All subjects were tested for VJ and kicking distance on 3 occasions: pre-test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 10 publications
6
51
1
4
Order By: Relevance
“…In the present study KD increased 8.8% for the EG while the CG did not change. Prior research reports increases in KD of 11.5% after 7-weeks of plyometric training in female adolescent players 13 and 22.5% after 12-weeks of plyometric training in pre-adolescent boys. 24 Whilst such rapid increases could potentially be due to age and maturation, Haldankar et al 27 reported 12-weeks of RT significantly improved KD in adult amateur soccer players (11.5%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study KD increased 8.8% for the EG while the CG did not change. Prior research reports increases in KD of 11.5% after 7-weeks of plyometric training in female adolescent players 13 and 22.5% after 12-weeks of plyometric training in pre-adolescent boys. 24 Whilst such rapid increases could potentially be due to age and maturation, Haldankar et al 27 reported 12-weeks of RT significantly improved KD in adult amateur soccer players (11.5%).…”
Section: Discussionmentioning
confidence: 92%
“…Prior research found 7 weeks of plyometric training produced increases in CMJ in amateur female soccer players of 8.3%. 13 However, whilst isometric knee extensor training may be less effective than plyometric training for increasing CMJ, isometric training is evidently an approach that may still benefit jump performance and some have argued that explosive training (such as plyometrics) may represent an unnecessary injury risk. 14,15 Potential mechanisms for improved CMJ may include increased tendon stiffness and rate of force development.…”
Section: Discussionmentioning
confidence: 99%
“…Issues regarding the translation of scientific data to shape and drive practice in soccer have been questioned previously (11). This is evident in the compliance of female soccer players to neuromuscular training programs which can improve physical performance (15,43,45) and reduce injury risk factors (12,44,50,51,57,59) when implemented successfully. Studies, however, often report poor compliance with the training intervention (1, 12,44,59) or poor intervention fidelity (29).…”
Section: Introductionmentioning
confidence: 99%
“…Plyometrics improved lower-body performance, especially in the areas of jump height and power 29 . And it is effective for increasing lower body anaerobic power like vertical jumping ability for both athletes and nonathletes 30,31,32,33,34 . Plyometrics exercises are not only effective in male it also effective in improving vertical jump in female 35 .…”
Section: Discussionmentioning
confidence: 99%